Convolution number and its application to elliptic integrals and the Schwarz-Christoffel transformation - Hassenpflug, W. C.(Walter Carl) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.